Lifestyle factors and risk of venous thromboembolism - Enga, Kristin Fjeldstad (2013)
The papers of this thesis are not available in Munin: 1. Enga KF, Braekkan SK, Hansen-Krone IJ, Wilsgaard T and Hansen JB.: 'Coffee consumption and the risk of venous thromboembolism. The Tromsø study', Journal of Thrombosis and Haemostasis (2011), vol. 9(7):1334-1339, available at http://dx.doi.org/10.1111/j.1538-7836.2011.04353.x 2. Enga KF, Brækkan SK, Hansen-Krone IJ and Hansen JB.: 'Emotional states and future risk of venous thromboembolism: the Tromsø Study', Thrombosis and Haemostasis (2012), vol. 107(3):485-493, available at http://dx.doi.org/10.1160/TH11-09-0667 3. Enga KF, Braekkan SK, Hansen-Krone IJ, le Cessie S, Rosendaal FR and Hansen JB.: 'Cigarette smoking and the risk of venous thromboembolism: the Tromsø Study', Journal of Thrombosis and Haemostasis (2012), vol. 10(10):2068-2074, available at http://dx.doi.org/10.1111/j.1538-7836.2012.04880.x 4. Enga KF, Braekkan SK, Skjeldestad FE and Hansen JB.: 'Socioeconomic status and the risk of venous thromboembolism – The Tromsø study' (manuscript) SUMMARY There is little knowledge about the association between lifestyle factors and risk of venous thromboembolism (VTE). The aim of this thesis was to investigate the relation between coffee consumption, emotional states, cigarette smoking and socioeconomic status and future risk of incident VTE in a prospective, population-based cohort study. Our study population consisted of more than 27 000 men and women, who participated in the fourth Tromsø study (1994-95). All adult inhabitants of the municipality of Tromsø, Norway, were invited to participate in the Tromsø study. Information about lifestyle factors and other relevant factors, were obtained by self-administered questionnaires, blood samples and a physical examination. The study subjects were followed until end of follow-up, December 31, 2010, and all VTE events occurring during this time period were registered. We found that coffee consumption was inversely associated with risk of VTE. Subjects who drank 3-6 cups of coffee daily had about 30% lower ...